Comment on: “Clinical Features, Management, and Prognosis of an International Series of 161 Patients With Limited-Stage Diffuse Large B-Cell Lymphoma of the Bone (the IELSG-14 Study)” - Hoppe, Richard (Oncologist, 2014)
The conclusion of Ventre et al. is that patients with primary diffuse large B-cell lymphoma (DLBCL) of bone should be treated with anthracycline-based chemotherapy (the standard for all cases of DLBCL) with or without radiotherapy. The study suffers from several weaknesses that make the conclusion doubtful.